2022
DOI: 10.3390/polym14214594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Irradiation at Different Stages of Manufacturing Unsaturated Polyester Nanocomposite

Abstract: The possibility of using microwave radiation at various stages of obtaining an unsaturated polyester composite modified with carbon nanotubes was studied. The optimal content of MWCNTs in the system was experimentally selected, having the best effect on the strength of the composite. The effect of the microwave field on the properties of a polyester composite during the microwave treatment of an oligomer, a polymerized composite, and MWCNTs before their addition into the oligomer was studied. The processes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…By combining straw and mud to create a mixture, bricks with improved resistance to squeezing and tearing can be made. These bricks are suitable for use as building blocks [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…By combining straw and mud to create a mixture, bricks with improved resistance to squeezing and tearing can be made. These bricks are suitable for use as building blocks [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…After finishing with octadecyl mercaptan containing a long carbon chain, SH-PET and CA-Fe-SH-PET both appeared as two obvious −CH 3 and −CH 2 characteristic peaks at 2915 cm −1 and 2847 cm −1 , whereas the 1640 cm −1 and 1619 cm −1 peaks disappeared for CA-Fe-SH-PET, indicating that mercaptan was grafted onto the PET through PCA adhering to the fabric by click chemical reaction. Since the SH peak is usually weak, no obvious characteristic peak was detected [18][19][20][21][22][23]. 1, it can be concluded that the carbon atom content on the surface of the PET fabrics treated with n-octadecyl mercaptan increased significantly.…”
Section: Surface Morphology and Chemical Structure Characterizationmentioning
confidence: 96%
“…In recent years, technologies related to the processing of polymeric materials in the microwave electromagnetic field (EMF) have been developed [26][27][28]. Studies of electrophysical methods of processing polymers and products have shown the efficiency of using the energy of a microwave electromagnetic field for the modification of polymer composite materials (PCM) based on thermosetting binders.…”
Section: Introductionmentioning
confidence: 99%